2020
DOI: 10.1111/mec.15422
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and evolutionary drivers of haemoplasma infection and bacterial genotype sharing in a Neotropical bat community

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(82 citation statements)
references
References 138 publications
(183 reference statements)
2
79
1
Order By: Relevance
“…(targeting the gltA gene) using previous diagnostic protocols (Bai, Gilbert, Fox, Osikowicz, & Kosoy, 2016; Volokhov et al, 2017). Hemoplasma data and sequences have been published previously (Becker, Speer, et al, 2020). Efforts to characterize Bartonella spp.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(targeting the gltA gene) using previous diagnostic protocols (Bai, Gilbert, Fox, Osikowicz, & Kosoy, 2016; Volokhov et al, 2017). Hemoplasma data and sequences have been published previously (Becker, Speer, et al, 2020). Efforts to characterize Bartonella spp.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we assessed infection with two bacterial pathogens, hemoplasmas and Bartonella spp. Both are common in Neotropical bats (Ikeda et al, 2017), including in these Belize sites (Becker, Bergner, et al, 2018;Becker, Speer, et al, 2020), and we previously showed infection can correlate with immunity in vampire bats specifically (Becker, Czirják, et al, 2018). However, how Hg shapes infection risk, and if such patterns are mediated by immunological relationships, is unknown.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, despite the enduring focus on virus ecology, more zoonoses are caused by bacteria than any other pathogen group (Han, Kramer, & Drake, 2016). To develop a more comprehensive understanding of zoonotic risk in bacteria, greater attention should be paid to whether the general patterns in zoonotic potential, pathogen richness and pathogen sharing observed for viruses persist for bacterial pathogens (Becker et al., 2020). In particular, theory suggests that high levels of phenotypic plasticity, low evolutionary rates and recombination ability typical of bacteria should reduce their propensity to specialize, which may generate distinct pathogen sharing patterns from viruses (Bonneaud, Weinert, & Kuijper, 2019).…”
Section: Figurementioning
confidence: 99%